PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Aulia Rizka Dwi Rachma; Deasy Ariyanti Rahayuningsih; Dicky Supriatna (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study to obtain empirical evidence related the internal and external influence of corporate factors on Corporate Social Responsibility Disclosure. The independent variables used in this study are Board Size, Audit Quality, Board of Director Ownership, Institutional Ownership, Profitability, Leverage, Audit Committee, and Media Exposure.This study used non-financial companies listed on Indonesia Stock Exchange (IDX) from 2019 to 2021. Researchers used purposive sampling in determining company samples, and 99 companies met the criteria in this study. In this study, the hypothesis was test using the multiple linear regression method. The result of this study show that Board Size has positive effect on CSRD, because the larger size of the board, thus higher the understanding and experience to make disclosures. Audit Quality has a positive effect on CSRD, because high audit quality can expand the disclosure made by the company. Leverage has a positive effect on CSRD, the company seeks to attract a good image from public for a good returns in the future. Meanwhile, other variables the Board of Director Ownership, Institutional Ownership, Profitability, Audit Committee, and Media Exposure, do not affect CSRD. Because it does not have a significant impact to motivate companies in making CSRD